Exercise is medicine! How to safely return to sports after COVID-19? A meta-analysis and a practical flowchart for cardiovascular risk assessment may help you - Colombo, C. (International Journal of Cardiovascular Sciences, 2022)
Exercise is medicine! Although this premise is well established, how to maintain this "treatment" for various diseases during the COVID-19 pandemic? This has been a concern of all doctors in the world since exercise contributes to the control of cardiovascular diseases and other comorbidities recognized as risk factors for a worse outcome in COVID-19. Moreover, it has already been shown that higher cardiorespiratory fitness is inversely associated with the likelihood of hospitalization due to COVID-19.